2018
DOI: 10.1186/s40168-018-0494-4
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bifidobacterium strains and galactooligosaccharides improve intestinal barrier function in obese adults but show no synergism when used together as synbiotics

Abstract: BackgroundOne way to improve both the ecological performance and functionality of probiotic bacteria is by combining them with a prebiotic in the form of a synbiotic. However, the degree to which such synbiotic formulations improve probiotic strain functionality in humans has not been tested systematically. Our goal was to use a randomized, double-blind, placebo-controlled, parallel-arm clinical trial in obese humans to compare the ecological and physiological impact of the prebiotic galactooligosaccharides (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
183
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(188 citation statements)
references
References 102 publications
3
183
0
2
Order By: Relevance
“…As discussed earlier, prebiotic intervention results in the elaboration of SCFAs that can act to improve barrier function in the gut and prebiotic intervention with GOS has shown improvements in barrier function in vivo. 115 Impaired barrier function can allow translocation of inflammatory mediators such as bacterial lipopolysaccharide (LPS) from the gut into systemic circulation, which has been termed metabolic endotoxaemia 116 and has been suggested to be a causative factor in diabetes and obesity according to evidence, albeit from studies in mice. 117,118 .…”
Section: [H1] Prebioticsmentioning
confidence: 99%
“…As discussed earlier, prebiotic intervention results in the elaboration of SCFAs that can act to improve barrier function in the gut and prebiotic intervention with GOS has shown improvements in barrier function in vivo. 115 Impaired barrier function can allow translocation of inflammatory mediators such as bacterial lipopolysaccharide (LPS) from the gut into systemic circulation, which has been termed metabolic endotoxaemia 116 and has been suggested to be a causative factor in diabetes and obesity according to evidence, albeit from studies in mice. 117,118 .…”
Section: [H1] Prebioticsmentioning
confidence: 99%
“…Although several other probiotics and commensal strains are also known to modulate gut microbiota and have shown beneficial effects on host health (3,54,55), their mechanisms of actions are not clear. Some probiotic strains are known to modulate immune cells to suppress inflammation, whereas others have been shown to enhance the intestinal barrier to reduce inflammation by reducing nonspecific leakiness of inflammatory substances from gut to immune sites (18,19). Nevertheless, these results remain correlative, as leaky gut induces inflammation and increased inflammation also promotes derangements in intestinal barrier functions to increase leakiness (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are one of the most accepted strategies to modulate the gut microbiota and normalize dysbiosis (13)(14)(15)(16)(17); therefore, we posit that probiotic therapy can maintain healthy gut microbiota and reduce leaky gut and inflammation. Several preclinical studies have shown that some specific probiotic strains may improve intestinal permeability homeostasis (18,19) and inflammation (20,21). Multiple studies also suggest that probiotics are beneficial for several human diseases, including obesity and diabetes (13)(14)(15)(16)(17)(21)(22)(23); however, the origin of such probiotics remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of both probiotics and prebiotics is called synbiotics (Gibson & Roberfroid, 1995). The ingestion of synbiotics is also expected to lead to a large increase in the number of bifidobacteria in the intestinal tract (Childs et al, 2014;Krumbeck et al, 2018;Macfarlane, Cleary, Bahrami, Reynolds, & Macfarlane, 2013;Shioiri et al, 2006). Unfortunately, because previous reports evaluated the bifidogenic effects of synbiotics compared with only placebo, not with probiotics directly, and studies did not result in a significant increase in the number of bifidobacteria compared with probiotics, it has not been shown definitively that synbiotics are clearly better than probiotics or prebiotics at increasing the number of bifidobacteria in the gut.…”
mentioning
confidence: 99%